2017
DOI: 10.4103/0259-1162.186601
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between epidural ropivacaine versus ropivacaine with clonidine in patients undergoing abdominal hysterectomy: A randomized study

Abstract: Context:Regional anesthesia has emerged as one of the preferred and convenient modes for intra- and post-operative management owing to its advantage of not interfering with the metabolic functions, better tolerability, and decrease in reflex activity. In recent years, ropivacaine has increasingly replaced bupivacaine as a preferred local anesthetic because of its similar analgesic properties, lesser motor blockade, and decreased propensity of cardiotoxicity. Neuraxial adjuvant such as clonidine used in epidura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Ropivacaine, a stereo-specific levorotary local anesthetic, has been widely utilized in peripheral nerve block analgesia (19). Compared with bupivacaine, ropivacaine exerts vasoconstrictor effects and has a lower cardiac toxicity risk, and therefore has been widely used in surgical analgesia (20,21). A previous report by Paut et al (22) showed that a maximum plasma concentration (C max) of >50% in children with FICB is more than twice the alert concentration of ropivacaine (2.2 µg/ml), without the occurrence of serious LAST, indicating that FICB may have a higher risk of LAST in specific populations.…”
Section: Introductionmentioning
confidence: 99%
“…Ropivacaine, a stereo-specific levorotary local anesthetic, has been widely utilized in peripheral nerve block analgesia (19). Compared with bupivacaine, ropivacaine exerts vasoconstrictor effects and has a lower cardiac toxicity risk, and therefore has been widely used in surgical analgesia (20,21). A previous report by Paut et al (22) showed that a maximum plasma concentration (C max) of >50% in children with FICB is more than twice the alert concentration of ropivacaine (2.2 µg/ml), without the occurrence of serious LAST, indicating that FICB may have a higher risk of LAST in specific populations.…”
Section: Introductionmentioning
confidence: 99%